HEMORRHAGIC DISEASE OF THE NEWBORN (World Bulletin of Public Health, 2024)
Hemorrhagic disease of the newborn (HDN) (ICD code – P53), or vitamin Kdependent hemorrhagic syndrome, is an acquired or congenital disease manifested by increased bleeding in newborns and children in the first months of life due to insufficiency of blood coagulation factors (II , VII, IX, X), the activity of which depends on vitamin K. The biological role of vitamin K is to activate the gamma-carboxylation of glutamic acid residues in prothrombin (factor II), proconvertin (factor VII), antihemophilic globulin B (factor IX) and Stewart-Prower factor (factor X), as well as in plasma antiproteases C and S, which play an important role in the anticoagulation system, as well as osteocalcin and other proteins.
Keywords: HDN; treatment; method